Employment Effects of Spatial Dispersal of Refugees - Anna Piil Damm; Michael Rosholm (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
We argue that spatial dispersal policies on refugees and asylum seekers influence labour market assimilation of refugees through two mechanisms: first, the local job offer arrival rate and, second, place utility. Our partial search model with simultaneous job and residential location search predicts that the reservation wage for local jobs decreases with place utility. We argue that spatial dispersal decreases average place utility of refugees which decreases the transition rate into first job due to large local reservation wages. We investigate both mechanisms empirically and test the predictions of the theoretical model by evaluating the employment effects of the Danish spatial dispersal policy carried out 1986-1998.
Keywords: 330; Migration